Isothermal Modeling Study Of Concentration Fluctuations In Multi-Jet Turbulent Mixing - Mustafa, Azeman; Andrew, G. E. (Penerbit UTM Press, 2005)

(untitled)
Water analogy flow visualisation and conductivity techniques with air bubbles and a salt solution as tracers are relatively simple and cost-effective techniques for the qualitative and quantitative studies of turbulent fuel and air mixing and yet give very useful information about aerodynamic patterns and mixing characteristics of the system concerned. These techniques have been used to study the fuel placement effects on the flow aerodynamics and mixing characteristics of a series of multi-jet grid cone stabilised non-swirl flow. The experimental results showed that the degree of fuel and air mixing was largely governed by the internally-generated flow aerodynamics and the turbulent energy available. The methods of direct-fuel- injection had a major influence on the mixing uniformity only in the high turbulence jet interaction zone near the cone exit plane